Partial stability and stabilization of dynamical systems - Kovalev, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove the theorem on necessary and sufficient conditions of partial instability and the theorem on partial stabilization of nonlinear dynamical systems. We obtain sufficient conditions of controllability for systems linear with respect to control. We also study the problem of control and stabilization of an angular motion of a solid body by rotors.